Rethinking Curriculum A Comparative Study of Pre-service Elementary Teacher Education Curriculum - Chauhan, Sonika (INDIAN EDUCATIONAL REVIEW, 2017)
This paper presents the results of a comparative study of revised pre-service teacher education curricula at the elementary stage of three states, namely Delhi, Chhattisgarh and Madhya Pradesh. The curriculum of the Diploma in Elementary Education (D.El.Ed) of all the states have been revised keeping in mind the principles and guidelines of National Curriculum Framework for Teacher Education (NCFTE 2009) developed by National Council of Teacher Education (NCTE). This study makes a modest attempt to examine the variations within teacher education curricula of three states. Through a method of documentary analysis, the present research examined the curricula of different states in terms of their course content, aims and objectives and the marks weightage given to each paper against NCFTE 2009. Results indicated that all the three states have developed their curriculum keeping in mind the vision of NCFTE and have geared their course structure from the overemphasis on theoretical learning into a combination of theory and practice. However, there are a few areas of concerns that need to be taken care of so as to prepare teachers who are reflective, competent and thinking professionals as envisaged by NCFTE 2009.